Attitudes Toward Gender-Neutral Spanish: Acceptability and Adoptability - Bonnin, Juan Eduardo; Coronel, Alejandro Anibal (Frontiers in Sociology, 2021)
This article presents the results of a survey conducted in January 2020 about attitudes toward gender-neutral language in Argentina. The survey was delivered mainly through social networks to 4,205 participants, and its results help understand the complexity of the attitudes toward the phenomenon. In particular, I will argue two hypotheses: 1) that an extensive favorable attitude of acceptance toward gender-neutral language does not imply extensive willingness to use it; 2) that its use is more readily accepted and used in vocative positions, indicating that it works better as a strategic discursive option than as an ongoing linguistic change.